State government land tax performance in Malaysia - Abdul Manaf, Nor Aziah (Universiti Utara Malaysia, 2006)
State Government Land Tax Performance is a specific book that discusses in detail land tax administration system in Malaysia. It provides an in-depth analysis of the efficiency, productivity, administration system, staff motivation and work commitment of the Malaysian land tax system. It also covers a systematic approach of literature review, research design, questionnaire development and data collection. This book proves invaluable for land tax administrators, land and mines officers, business consultants, researchers, academics and society. Public Administration students will find this book which has useful contents, findings and discussions useful, thus giving a real grasp of the administration system and its practice.